Dentists' Habits of Antibiotic Prescribing May be Influenced by Patient Requests for Prescriptions - Aceil Al-Khatib; Raneem Ahmad AlMohammad (Hindawi Limited, 2022)
Objective. This study evaluates dentists' antibiotic prescribing habits and the frequency of facing patient pressure for prescriptions. Methods. An online anonymous survey was used to collect data on antibiotic prescribing practices, including prescribing unnecessary antibiotics if requested by patients. Results. The study population included 345 dentists; 227 (65.8%) were females and 118 (34.2%) were males. 54 (15.7%) reported that they prescribed unnecessary antibiotics more than once per week, 47 (13.6%) once per month, 135 (39.1%) rarely, and 109 (31.6%) never prescribed unnecessary antibiotics. 117 (33.9%) reported being pressured by patients to prescribe unnecessary antibiotics more than once per week. 110 (31.9%) reported being pressured by patients to do so at least once per month. There was a statistical difference between the two genders (P<0.001) in reporting that patients pressured them to prescribe antibiotics when antibiotics were not necessary for treatment or prophylactic purposes and in prescribing unnecessary antibiotics sometimes if requested by a patient (P=0.008). In addition, there was a statistical difference in dentists' confidence in their knowledge and practice in the area of antibiotic prescribing (P<0.001). Conclusions. The results show that unnecessary antibiotic prescribing by dentists can be influenced by patient pressure.